Hyperbaric oxygen therapy in the ATLS/ACLS resuscitative management of acutely ill or severely injured patients with severe anemia: a review - Van Meter, Keith W. (Frontiers in Medicine, 2024)
For short periods of time, even without the presence of red blood cells, hyperbaric oxygen can safely allow plasma to meet the oxygen delivery requirements of a human at rest. By this means hyperbaric oxygen, in special instances, may be used as a bridge to lessen blood transfusion requirements. Hyperbaric oxygen, applied intermittently, can readily avert oxygen toxicity while meeting the body's oxygen requirements. In acute injury or illness, accumulated oxygen debt is shadowed by adenosine triphosphate debt. Hyperbaric oxygen efficiently provides superior diffusion distances of oxygen in tissue, over and above that provided by breathing normobaric oxygen. Intermittent application of hyperbaric oxygen can resupply adenosine triphosphate for energy for gene expression for reparative and anti-inflammatory cellular function. This advantageous effect is termed the hyperbaric oxygen paradox, much the same as intermittent normobaric oxygen has been used to elicit erythropoietin expression which has been termed the normobaric oxygen paradox. Reperfusion injury after ischemic insult can be ameliorated by hyperbaric oxygen administration. Oxygen toxicity can be averted by short hyperbaric oxygen exposure times with air breaks during treatments and also by lengthening the time between hyperbaric oxygen sessions as the treatment advances. Hyperbaric chambers can be assembled to provide everything available to a patient in modern-day intensive care units. The complication rate of hyperbaric oxygen therapy is very low. Accordingly, hyperbaric oxygen, when safely available in hospital settings, should be considered as an adjunct for the management of critically injured or ill patients with disabling anemia.